2006
DOI: 10.1111/j.1467-2494.2006.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

An interlaboratory comparison of methods used to assess antioxidant potentials1

Abstract: Many analytical methods are used to measure the antioxidative activity of substances yet little is known about the comparability of the test results between laboratories. After an initial evaluation of a broad range of methods conducted by one laboratory, the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, the trolox equivalent antioxidant capacity (TEAC) assay, the lipid assay (or 2,2'-azobis(2-aminepropane) (ABAP) assay) and the thiobarbituric acid (TBA) assay were selected to be evaluated in the interlaboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 27 publications
(23 reference statements)
2
37
0
Order By: Relevance
“…Therefore, the use of at least two different analytical approaches to test the antioxidant capacity of specific substrates is recommended. [39] Buenger et al [40] reported that the DPPH˙ assay, followed by the ABTS˙+ assay, yield the best results (based on reproducibility and sensitivity). These tests, involving chromogen compounds of a radical nature, are also the most common antioxidant capacity assays, used for their ease, speed and sensitivity.…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…Therefore, the use of at least two different analytical approaches to test the antioxidant capacity of specific substrates is recommended. [39] Buenger et al [40] reported that the DPPH˙ assay, followed by the ABTS˙+ assay, yield the best results (based on reproducibility and sensitivity). These tests, involving chromogen compounds of a radical nature, are also the most common antioxidant capacity assays, used for their ease, speed and sensitivity.…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…However, the action of free radicals and active oxygen can be balanced by a system of antioxidant defenses, including antioxidant compounds and enzymes (Gutteridge & Halliwell, 1992). Synthetic compounds such as butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA) and tertiarybutylhydroquinone (TBHQ), are widely employed as preservatives in the food and pharmaceutical industry nowadays (Buenger et al, 2006). But there are numerous reports on adverse effects of synthetic antioxidants such as toxicity and carcinogenicity (Chotimarkon et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It reported that these assays require relatively standard equipment and yield the fast and most reproducible results (Buenger et al, 2006). From these results, it was demonstrated that the n-BuOH fraction from 70% EtOH crude extract of Prunella vulgaris var.…”
Section: Discussionmentioning
confidence: 70%